Detection of Retinal and Choriocapillaris Microvascular Changes in Retinal Vein Occlusion and Fellow Eyes by Optical Coherence Tomography Angiography: A Systematic Review and Meta-Analysis - Linxin Wei; Qing Zhao; Youxin Chen (Ophthalmology and Therapy)
Abstract Introduction This study aims to summarize the retinal and choroidal microvascular features detected by optical coherence tomography angiography (OCTA) in the affected and fellow eyes of patients with retinal vein occlusion (RVO). Methods A comprehensive search of the PubMed, Embase, and Ovid databases was conducted to identify studies comparing OCTA metrics among RVO, RVO-fellow, and control eyes. Outcomes of interest included parameters related to foveal avascular zone (FAZ) and fovea- and optic nerve head (ONH)-centered perfusion measurements of superficial capillary plexus (SCP), deep capillary plexus (DCP), and choriocapillaris layer. Pooled results were presented as mean differences or standardized mean differences with 95% confidence intervals. Results Fifty-three studies, comprising 2119 RVO, 1393 fellow, and 1178 control eyes, were included in the quantitative meta-analysis. RVO eyes exhibited larger FAZ areas, increased FAZ acircularity, and reduced macular retinal and choriocapillaris perfusion compared to RVO-fellow and control eyes (P < 0.05). RVO eyes also demonstrated significantly lower perfusion density (PD) in the inside-disk and peripapillary regions of the radial peripapillary capillary layer (RPC), as well as lower retinal and choriocapillaris PD in the 4.5 × 4.5 mm2 field of view (FOV) of ONH-centered scans (P < 0.05). RVO-fellow eyes showed decreased SCP-PD and DCP-PD in the parafoveal region and the 3 × 3 mm2 FOV, reduced inside-disk and 4.5 × 4.5 mm2 FOV RPC-PD (P < 0.05), and a diminished choriocapillaris flow area in the 3 × 3 mm2 FOV (P < 0.05). Conclusions Both RVO-affected and RVO-fellow eyes exhibited retinal and choriocapillaris microvascular impairment around the fovea and ONH. OCTA represents a promising tool for comprehensively assessing vascular alterations in RVO and providing evidence of fellow eye involvement.